Moisture sorption isotherms and thermodynamic properties of whole black peppercorns (Piper nigrum L.). Issue 1 (November 2015) - Yogendrarajah, Pratheeba; Samapundo, Simbarashe; Devlieghere, Frank; De Saeger, Sarah; De Meulenaer, Bruno
Abstract Adsorption and desorption isotherms for whole black peppercorns (Piper nigrum L.) were developed at 22, 30 and 37 °C using standard static gravimetric method. The sorption isotherms exhibited a type III behaviour according to Brunauer-Emmett-Teller (BET) classifications. The equilibrium moisture content (EMC) decreased with increasing temperature at a particular water activity (aw). Hysteresis existed over the entire aw range at 30 and 37 °C. At 22 °C, an intersection of the curves was found at aw closer to 0.75. The goodness of fit of the models was evaluated using several statistical indices and residual plots. The Guggenheim-Anderson-de Boer (GAB) and Peleg models were determined to best describe the experimental sorption data. The monolayer moisture content (M0) were 4.78, 3.56 and 3.49 g/100 g at 22, 30 and 37 °C for adsorption. The maximum isosteric heat of sorption was 28.1 and 73.3 kJ/mol for adsorption and desorption, respectively. The net isosteric heat of sorption and sorption entropy increased with increase in EMC; both curves dropped off exponentially after M0. The Gibbs free energy change for adsorption ranged from 100.6 to 9370.6 J/mol. The black peppercorns can be stored at 22, 30 and 37 °C, by reducing their MC to 10, 8 and 7 g/100 g, respectively, with aw below 0.60.